A brain imaging study of dopamine receptor D2 availability in cannabis dependent users after recovery from cannabis-induced psychosis - Weinstein, Aviv M. (Frontiers in Psychiatry, 2023)
There is increased risk of psychosis associated with cannabis use disorder and the interaction of THC with dopamine neurotransmission is complex. It is important to investigate the recovery from cannabis-induced psychosis and its effects on the brain’s dopamine neurotransmission. This study was to evaluate dopamine receptor D2 availability in the striatum (caudate/putamen) in recently abstinent cannabis dependent users after recovery from psychosis in comparison with abstinent MDMA “ecstasy” abusers and healthy control participants. Participants were eight abstinent ex cannabis-dependent users who were treated for cannabis-induced psychosis with anti-psychotic medication and psychosocial support for 4 months in an inpatient treatment center for drug users. They were compared with nine abstinent ex MDMA “ecstasy” abusers who received medication and psycho-social treatment for 4 months at the same treatment facility and eight healthy control participants. All participants were scanned with bolus and constant infusion of [123I] Iodobenzamide (IBZM) in Single Photon Computed Tomography (SPECT). Cannabis abstinent users who were treated for cannabis-induced psychotic episodes showed no difference in dopamine D2 receptor availability in the caudate compared with abstinent MDMA “ecstasy” abusers and healthy control participants. This finding indicates minimal effects of cannabis-induced psychosis on dopamine reward mechanisms. There is evidence for reduced D2 receptor availability measures in the right putamen (uncorrected) which may indicate a residual effect of anti-psychotic medication.